Chemical Evolution of Solutions from Beans Soaking and Cooking Processes: Case Study of Phaseolus Vulgaris L. (Global Journal of Science Frontier Research, 2021)
The present paper aims to highlight the physico-chemical evolution of solutions from soaking and beans cooking processes. For that purpose, solutions from soaking were produced by putting in contact 2kg of sorted and quickly washed beans seed with 8kg of water with known physico-chemical characteristics. Concerning the solutions from cooked beans, they were produced by putting on fire the pot containing the mixture of the water from soaking and bean seeds. The beans were a variety of Phaseolus vulgaris L., known as "Meringue". The cooking process was done without salts. The samples of solutions were collected as follow: 30 and 60 minutes respectively after the beginning of the soaking, 30, 60, and 90 minutes after the beginning of the cooking process of the beans soaked during 60 minutes. After each sampling, the equal volume of the solution collected was replaced with the water used for the cooking process. Solutions obtained from beans soaking and beans cooking gradually enriched in mineral salts, particularly major macro elements (N and K), minor macro elements (Ca, S, Mg), and oligoelements compared to the situation noticed in the water used for the cooking process.
Keywords: waste water; sanitation; recycling; fertilization; agriculture; nutrition; temperature